Radiotherapy and cancer status in Latin America: economic analysis of investment opportunities up to 2030. (July 2022) - Sarria, Gustavo R; Martinez, David A; Del Castillo, Ruben; Salgado, Apolo; Pinillos, Luis; Felix, Armando; Bobadilla, Ivan; Ferraris, Gustavo; Polo, Alfredo; Sarria, Gustavo J
Abstract: Background: Timely access to radiotherapy treatments for cancer in Latin America is hindered by substantial delays in investment. We herein report on the current incidence of the ten most frequent malignancies and on radiotherapy-related logistics across Latin America with the objective of identifying resource gaps and facilitate the planning of health-care investments up to 2030. Methods: Data were collected from the International Atomic Energy Agency's (IAEA) Directory of Radiotherapy Centers and matched to open-source databases and individual surveys sent to national scientific societies in participant countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Paraguay, Peru, Uruguay, and Venezuela). Demographic, economic, and epidemiological data were gathered from the World Bank and the Global Cancer Observatory registries. The incidence rates of the ten most common cancers treated with radiotherapy in each country were multiplied by the respective radiotherapy use rate according to the IAEA's Time-Driven Activity-Based-Costing model. Country-specific adjustments were made and the following assumptions were factored for the analysis: 240 working days, 60 patients treated per teletherapy unit per day, and 25 external beam radiotherapy fractions required per diagnosis at a cost of US$ 1703·75 or equivalent per full treatment, and four brachytherapy fractions for cervical (75% of total) and endometrial (27%) cancer and one boost fraction for prostate cancer (5%) diagnosis, at a cost of US$ 1426·40 per treatment. These values were adopted from India (for cervix cancer data) and Spain (endometrial cancer data), which are countries with a cancer incidence profile similar to that of Latin America. The prostate brachytherapy use rate was adopted from recently published US data. Human resource requirements were estimated according with the observed annual cancer incidence, keeping with IAEA's recommendations. 10-year incidence and costs projections were calculated according to the estimated demography dynamics and time value of money equation for each country for the period 2020–30. Current and projected cancer incidences and radiotherapy, personnel, and logistic requirements are reported through absolute numeric differences and mean values. Potentially saved lives (equivalent to 50% of newly included patients after increasing radiotherapy capacities to recommended levels) and monetary return, assumed as a mean regional monthly wage multiplied by the rescued life-years, are also reported. Findings: Information concerning the 11 most populous countries in Latin America was obtained. As of 2020, a population of 557 213 447 individuals was recorded, accounting for 85% of the Latin American inhabitants and projected to increase to 772 038 620 (an increase of 214 825 173) by 2030. The 2020 overall cancer incidence was 1 055 892 cases and the mean 2020 incidence per country was 95 990 (SD 135 013). The 10-year projection was of 1 460 154 new cases with a mean of 132 741 (SD 188 832) per country, highlighting the high variability in needs across the region. Overall external beam radiotherapy use rate was estimated for 663 236 annual new cases in 2020, versus 916 592 annual new cases by 2030, and overall brachytherapy use was estimated for 90 428 annual new cases in 2020 and 125 152 annual new cases by 2030. The 2020 regional availability of treatment fractions was 11 822 400 for external beam radiotherapy and 216 960 for brachytherapy. Conversely, the 2020 required number of fractions was 13 241 088 (+12·2%) for external beam radiotherapy and 361 672 (+66·7%) for brachytherapy; and the projected required number of fractions in 2030 is 18 324 720 (+55·0%) for external beam radiotherapy and 500 744 (+130·8%) for brachytherapy. If the projected demand was to be covered, an additional 181 622 lives could potentially be saved by 2030, accounting for a 2-year total financial return of US$ 1 963 776 038·20, assuming 50% of additionally treated patients will be reincorporated to the economically active population. Interpretation: Bridging the gap in radiotherapy up to 2030 will save lives and reduce the financial toxicity of cancer management in Latin America. Governmental and private investment in radiotherapy is urgently required to shorten access disparities and reach these goals. Funding: None.